Influence of Social Networks amongst Undergraduates in Higher Educational Institutions - Kariapper, RKAR. (International Journal of Psychosocial Rehabilitation, 2020)
These days society is being mesmerized of the words “Social networks” and “socially networked individuals” respectively. The same is applicable to the university community specially undergraduates.More number of undergraduates are almost addicted to the social network tools such as Facebook, WhatsApp, Twitter, YouTube and LinkedIn in despite of original purpose of the tools. In fact, the undergraduates have started to utilize the social networks for networking, entertainment, learning and etc. Ongoing study shows that roughly 95% of the undergraduates have been using the social networks during the academic hours or off academic hours. End user privacy is under alarming level in despite of plat forms, devices and accessibility to the internet when the social network tools are being used. Learning environment, confidentiality, privacy, motivation, ease of use, availability, effect on health, satisfaction, file sharing and storage are the major challenging factors in contemporary social networking tools and social network users, especially undergraduates must be knowing on all those characteristics for proper use of social network and to protect themselves from unwanted issues. This research work analyses the most interesting issues among popular Social Networks media and direct undergraduates to focus on their education in a proper way. Facebook is a prominent social networking tool among undergraduates though it partially contributes to the academic activities. Most students desire to use WhatsApp due to the security and user friendliness (convenient functions) comparing with other social networks. This study answers, better social network tools for educational activities in its own capacity.